A realistic tolerant solution of a system of interval linear equations with the use of multidimensional interval arithmetic - Piegat, Andrzej; Pluciński, Marcin (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents a method of determining the robustness of solutions of systems of interval linear equations (ILEs). The method can be applied also for the ILE systems for which it has been impossible to find solutions so far or for which solutions in the form of improper intervals have been obtained (which cannot be implemented in practice). The research conducted by the authors has shown that for many problems it is impossible to arrive at ideal solutions that would be fully robust to data uncertainty.
Keywords: interval arithmetic; interval linear equation system; tolerable solution; multidimensional interval arithmetic